EFL Students’ Perception of Online Learning During Covid-19 in SMP Negeri 3 Busungbiu - Darmiyani, Ketut (STKIP AGAMA HINDU SINGARAJA, 2023)
This study focused on investigating EFL students’ perception towards online learning during Covid-19 in SMPN 3 Busungbiu. This study used mixed method research design. This method is the combination of qualitative and quantitative approach in gaining complete understanding of students’ perception. The data were collected through questionnaire and interview. The questionnaire consists of 25 items. The participants in this study were 7th grade students in SMPN 3 Busungbiu. The result found that the 7th grade students in SMPN 3 Busungbiu had a positive perception towards online learning during Covid-19. They had positive perception in the perceived usefulness and perceived instructor characteristics dimensions. They felt online learning was useful to be implemented during Covid-19 and the teacher also motivated, encouraged them to express their opinion, and gave them sufficient time to submit assignments. Meanwhile for the perceived ease of use dimension, it got neutral perception because they felt difficulty in understanding the material taught online, experienced challenges, and had difficulty socializing with others during the online learning.